Growth and structural characterization of RbTi1−xGexOPO4 crystals - Vilalta, A; Carvajal, J; Peña, A; Massons, J; Díaz, F; Aguiló, M (Elsevier, 2008)
RbTi1−xGexOPO4 single crystals were successfully grown from fluxes containing WO3. The evolution of the cell parameters with the content of Ge and the temperature was analyzed. The thermal expansion coefficients for RbTi0.965Ge0.035OPO4 obtained resulted in a much-reduced thermal anisotropy when compared with RbTiOPO4 (RTP). The Curie temperature of this material dramatically shifted to lower temperatures when Ge is present in the crystals, and it decomposes at a lower temperature when compared with RTP. Morphologically, we observed that the {1 0 0} form tended to disappear in the final shape of the crystals containing Ge. Finally, the second-harmonic generation efficiency of RbTi0.965Ge0.035OPO4 crystals is reduced to a quarter of that exhibited by RTP, when measured by the powder technique.